Effects of various solvent concentration, liquid-solid ratio, temperatures and time values on the extraction yield of anthocyanin from Vietnam Hibiscus sabdariffa L. (Roselle) - Pham, Tri Nhut; Nguyen, Thuong Nhan Phu; Lam, Tri Duc; Tran, Thien Hien; Nguyen, Duy Chinh; Vo, Dai-Viet N.; Le, Xuan Tien; Do, Sy Trung; Bach, Long Giang (IOP Publishing, 2019)
Nowadays, the trends in human health and fossil fuel dependent markets present opportunities for agricultural crops as renewable sources in several substitutes of synthetic components in clothing, fuels, and food. This research focused on anthocyanins along with protocatechuic acid and quercetin, which have been recognized as bioactive compounds in Hibiscus sabdariffa L. aqueous extracts. Laboratory extraction study was conducted on various solvent concentration, liquid-solid ratio, temperatures and time values on the extraction yield of anthocyanin from Vietnam Hibiscus sabdariffa L. (Roselle). On theother hand, total anthocyanins wereinvestigated in Hibiscus sabdariffa L. extract as μg/mL cyanidin-3-glucoside (cyd-3-glu). Extraction temperature of 60°C using solvent concentration 50%, extraction time of 30 min at liquid-solid ratio of 8:1 showed the highest anthocyanin recovery at 180,821 mg/L. Overall, Vietnam Hibiscus sabdariffa L. (Roselle) are responsive to anthocyanin extraction, making it an appropriate substrate for the development of industrial colorants and dyes.